Re-orientating experiences: Considerations for student development through virtual mobility in STEM (Journal of Applied Learning and Teaching, 2022)
Outbound mobility experiences (OMEs) provide a catalyst for learning environments that foster student development to occur in a global context. In STEM, OMEs foster critical thinking, creativity and scientific literacy. However, the sudden disruption to international travel due to the recent global pandemic has seen countries worldwide plunged into lockdown and borders closed. While the shift to online learning has been challenging, it has also provided the higher education sector an opportunity for wider implementation of online experiential learning environments, such as virtual mobility. Currently there has been little exploration of the potential of transforming physical, short-term, face-to-face mobility programs to an online environment for undergraduate science, technology, engineering and mathematics (STEM) students. This paper seeks to understand how we can meet the desired program outcomes of a physical OME to support critical thinking of undergraduate natural science students, when the OME occurs online.